1981
DOI: 10.1042/bj1930379
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a thermostable glucoamylase from the thermophilic fungus Thermomyces lanuginosus

Abstract: Glucoamylase (1,4-alpha-D-glucan glucohydrolase, EC 3.2.1.3) was purified from the culture filtrates of the thermophilic fungus Thermomyces lanuginosus and was established to be homogeneous by a number of criteria. The enzyme was a glycoprotein with an average molecular weight of about 57 000 and a carbohydrate content of 10-12%. The enzyme hydrolysed successive glucose residues from the non-reducing ends of the starch molecule. It did not exhibit any glucosyltransferase activity. The enzyme appeared to hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…an a-amylase, an a-glucosidase, and a glucoamylase. In static culture, Basaveswara Rao et al (1979) found that among four thermophilic fungi tested Thermomyces lanuginosus produced the highest specific activity of glucoamylase (52.1 U . mg protein-I), but in contrast to the present investigation the presence of other amylolytic activities was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…an a-amylase, an a-glucosidase, and a glucoamylase. In static culture, Basaveswara Rao et al (1979) found that among four thermophilic fungi tested Thermomyces lanuginosus produced the highest specific activity of glucoamylase (52.1 U . mg protein-I), but in contrast to the present investigation the presence of other amylolytic activities was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Basaveswara Rao et al (1981) have purified a glucoamylase from the culture filtrate of Thermomyces lanuginosus. This enzyme was a glycoprotein with an average molecular weight of about 57 000 and a carbohydrate content of 10-12%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial Purification of T. lanuginosus Glucoamylase. A culture of Thermomyces Zunuginosus ML-M was generously donated by V. Basaveswara Rao of the Indian Institute of Science, Bangalore, India, and grown in liquid culture as described (Basaveswara Rao et al 1981). Flasks were incubated at 50°C and shook at 250 rpm.…”
Section: Product Analysismentioning
confidence: 99%
“…Enzymes produced by thermophilic fungi are usually more thermostable than those produced by mesophilic fungi. Thermomyces lanuginosus is a thermophilic fungus that grows optimally between 48 and 52°C and secretes a variety of degradative thermozymes including: amylase (Odibo and Ulbrich-Hofmann, 2001), glucoamylase (Basaveswara Rao et al, 1981), hemicellulases (Lin et al, 1999;Singh et al, 2000a), lipase (Arima et al, 1972), phytase (Berka et al, 1998), serine-protease (Hasnain et al, 1992) and xylanases (Bennet et al, 1998;Gruber et al, 1998;Singh et al, 2000b;Singh et al, 2000c). Endo-b-1,4-xylanases (EC 3.2.1.8) from T. lanuginosus are extremely thermostable enzymes.…”
Section: Introductionmentioning
confidence: 99%